ANALISIS DAMPAK GRATIS ONGKOS KIRIM DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN PADA E - COMMERCE SHOPEE - WISNU YUSDITARA; HANNA MEILANI DAMANIK; MARTIN LUTER PURBA; HENDRIK E.S. SAMOSIR (JURNAL ILMIAH KOHESI, 2022)
Competition between fellow e-commerce is getting tougher, especially during the covid pandemic because of the limitationsof people to go out of the house, e-commerce buying and selling sites are one of the safest places to buy the productsneeded. Public image of the brand and the absence of product delivery costs will affect purchasing decisions.They conducted the study on 62 respondents using the dummy variable regression method to see their purchasingdecisions. The results show that a good brand image will improve product purchasing decisions while consumers will bemore interested in buying products on the day Shoppe provides many free shipping vouchers.